The effect of muscle mass recruitment on postprandial lipaemia - Muhammad Iskandar Ahmad Fajar. (2013)
Purpose: The present study examined a potential mechanism via which resistance exercise may modify triacylglycerol (TG). Methods: Five healthy males participated in three trials, with intervals of at least 7 but no more than 14 days apart, in random counterbalanced design: control (CT), single leg (SL) and double leg (DL). Participants came for Day 1 of trials at 1700 and did CT, SL or DL trial. They were given standardized dinner. Day 2 started at 0800 the following day. A high fat meal (1.21 g fat, 0.62 g carbohydrate and 0.29 g protein; and 58.6kJ energy.kg-1 body mass) was administered in the morning after each trial. Blood sample was taken in fasted state and 4 more times at hourly intervals. Results: There was no significant difference in the total area under curve (AUC) between trials (mean ± SD): CT 7.76 ± 3.34 mmol.4h.L-1 vs SL 8.01 ± 2.02 mmol.4h.L-1 vs DL 9.02 ± 3.44 mmol.4h.L-1, P = 0.516 and in the incremental AUC: CT 3.83 ± 2.26 mmol.4h.L-1 vs SL 4.12 ± 1.46 mmol.4h.L-1 vs DL 4.98 ± 2.74 mmol.4h.L-1, P = 0.399. There was also no time x trial interaction for repeated measures using ANOVA 2-way between trials and time (P = 0.599). Conclusion: These results show that difference in muscle mass recruitment during resistance training has no effect on postprandial lipaemia and eliminates a potential mechanism that can be used to reduce postprandial lipaemia.